2007
DOI: 10.3103/s1068373907110064
|View full text |Cite
|
Sign up to set email alerts
|

Anthropogenically modified natural background and its formation in the Russian freshwater ecosystems

Abstract: Results of generalized long-term data of hydrochemical monitoring of pollution of freshwater ecosystems in the most developed economic regions of Russia are presented. The factors responsible for the anthropogenically modified natural background of priority pollutants are described in detail and the most polluted water objects are evaluated.The environmental equilibrium of natural complexes of each region is the upper limit in economic development of Russia. The limit of this excess should be prevented by all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 1 publication
0
7
0
1
Order By: Relevance
“…-a constant but a little less high level of the nickel content in the Hauki-Lampi-Yoki (MFO = 13-25 MPC) and Luottn-Yoki (MFO = 8-12 MPC); -a constant, not exceeding 5 MPC level of the nickel content in the Pechenga River; -an episodic (1)(2)(3)(4) level of the nickel content in the Patso-Yoki River. A stable and very high level of pollution with copper compounds is characteristic of the mouth section of the Nyuduai River (MFO = 50-100 MPC).…”
Section: Assessment Of the Kola North Water Body Pollution Levelmentioning
confidence: 99%
See 1 more Smart Citation
“…-a constant but a little less high level of the nickel content in the Hauki-Lampi-Yoki (MFO = 13-25 MPC) and Luottn-Yoki (MFO = 8-12 MPC); -a constant, not exceeding 5 MPC level of the nickel content in the Pechenga River; -an episodic (1)(2)(3)(4) level of the nickel content in the Patso-Yoki River. A stable and very high level of pollution with copper compounds is characteristic of the mouth section of the Nyuduai River (MFO = 50-100 MPC).…”
Section: Assessment Of the Kola North Water Body Pollution Levelmentioning
confidence: 99%
“…The analysis of results of long-term observations over the water courses in different Russian regions results in the formation of a new "anthropogenically changed" environmental state, when the trophic status changes and the ecological capacity and, consequently, water ecosystem stability much decrease [3,4].…”
mentioning
confidence: 99%
“…The results of the analysis of the long-term regime information in this area showed that phenols (112 MPC), petroleum hydrocarbons (41 MPC), iron (31 MPC), copper (25 MPC), and manganese (24 MPC) compounds, whose concentrations were often above 10 MPC, should be referred to priority pollutants. RUSSIAN The upper boundaries of the anthropogenically modified background formed [4] exceeded the MPC of petroleum hydrocarbons and iron and copper compounds by 13-15 times, of ammonium nitrogen, phenols, and manganese compounds, by 5-6 times. It is reasonable to expect that heavy loading impact of river ecosystems persisted over the entire water area of the Ob and Taz estuarine area.…”
Section: Consequences Of Impact Of the River Influx Of Dissolved Chemmentioning
confidence: 99%
“…The Volga delta was found to be less contaminated than the Rhine and Danube deltas, possibly because potential pollutants were still trapped in upstream river sediments and floodplains (Winkels et al 1998). A few recent publications reported that the surface water in the Volga catchment area, especially in the River Oka region, was contaminated with organic and inorganic pollutants (Nikarnorov et al 2007; Moiseenko et al 2008). In the Ivankovo reservoir, located in the Volga River valley, heavy metals were accumulated in the upper humus horizon of the sediment and flooded riverside soils (Titaeva et al 2007).…”
Section: Introductionmentioning
confidence: 95%
“…The discharge of untreated or partly treated wastewater as well as the runoff from land surface results in contaminations of rivers and their floodplains with heavy metals and/or persistent organic pollutants (POPs; Baborowski et al 2004;Antić et al 2006;van der Veen et al 2006;Nikarnorov et al 2007; Moiseenko et al 2008). In river water, the majority of the pollutants is associated with suspended particulate matter (Morales et al 2007;Pepelnik et al 2005), which can be aggregated to freshwater flocs (Droppo et al 1997).…”
Section: Introductionmentioning
confidence: 97%